KINERJA AKTIFA PRODUKTIF PERUSAHAAN OTOMOTIF DALAM MEMACU PROFITABILITAS DALAM SITUASI EKONOMI YANG KURANG KONDUSIF - Asraf Asraf; Mardahleni Mardahleni; Alwizon Alwizon (ITB AAS Indonesia Surakarta, 2023)
The challenge for a number of companies after the Covid-19 Pandemic is to carry out the recovery process to return to normal. During the pandemic and post-pandemic, various strategies are needed for the industry to maintain the level of profitability or at least be able to survive at a safe level of profitability or even survive lest it experience burdensome losses for the continuity of the company. This study will analyze how the receivables strategy can contribute to the profitability of Automotive Industry companies in Indonesia. The analysis was conducted on 14 automotive companies listed on the Indonesia Stock Exchange by examining the effect of receivables turnover on the profitability ratios (ROA, ROE and NPM). The results showed that receivables did not have a significant effect on profitability ratios. This suggests that in the case of the automotive industry, the receivables strategy does not significantly contribute to efforts to sustain profitability in the Indonesian automotive industry. These findings indicate that financial institutions continue to play an important role in supporting sales and facilitating customer credit purchases.